J004457+4123 (Sharov 21): not a remarkable nova in M 31 but a background quasar with a spectacular UV flare - Meusinger, H.; Henze, M.; Birkle, K.; Pietsch, W.; Williams, B.; Hatzidimitriou, D.; Nesci, R.; Mandel, H.; Ertel, S.; Hinze, A.; Berthold, T. (2010)
Aims: We announce the discovery of a quasar behind the disk of M 31, which was previously classified as a remarkable nova in our neighbour galaxy. It is shown here to be a quasar with a single strong flare where the UV flux has increased by a factor of 20. The present paper is primarily aimed at the remarkable outburst of J004457+4123 (Sharov 21), with the first part focussed on the optical spectroscopy and the improvement in the photometric database. Methods: We exploited the archives of photographic plates and CCD observations from 15 wide-field telescopes and performed targetted new observations. In the second part, we try to fit the flare by models of (1) gravitational microlensing due to a star in M 31 and (2) a tidal disruption event (TDE) of a star close to the supermassive black hole of the quasar. Results: Both the optical spectrum and the broad band spectral energy distribution of Sharov 21 are shown to be very similar to that of normal, radio-quiet type 1 quasars. We present photometric data covering more than a century and resulting in a long-term light curve that is densely sampled over the past five decades. The variability of the quasar is characterized by a ground state with typical fluctuation amplitudes of 0.2 mag around barB 20.5, superimposed by a singular flare of 2 yr duration (observer frame) with the maximum at 1992.81. The total energy in the flare is at least three orders of magnitudes higher than the radiated energy of the most luminous supernovae, provided that it comes from an intrinsic process and the energy is radiated isotropically. The profile of the flare light curve is asymmetric showing in particular a sudden increase before the maximum, whereas the decreasing part can be roughly approximated by a t-5/3 power law. Both properties appear to support the standard TDE scenario where a 10 M_⊙ giant star was shredded in the tidal field of a 2...5×108 M_⊙ black hole. The short fallback time derived from the observed light curve requires an ultra-close encounter where the pericentre of the stellar orbit is deep within the tidal disruption radius. This simple model neglects, however, the influence of the massive accretion disk, as well as general-relativistic effects on the orbit of the tidal debris. Gravitational microlensing probably provides an alternative explanation, although the probability of such a high amplification event is very low.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics; black hole physics; galaxies: individual: M 31; gravitational lensing: micro; quasars: general; quasars: individual: J004457+4123